Pembelajaran Seni Pertunjukkan untuk Anak Usia Dini di Masa Pandemi dengan Local Genius Knowledge - Fauziah, Wiedy Putri; Fitriyah, Nur (Universitas Pendidikan Indonesia Kampus Serang, 2020)
Early childhood education is the important for a nation generation. It is the potential period in the growth of children to gain exploration experience from all aspects of both motoric and psychomotor. Lack of knowledge, especially about the concept and purpose of performing arts from an early age for education influence the design of learning programs that tend to be less creative. Even though in motion, there are many ways where the teacher can creatively connect with the values of student life at large the need of well-designed performing arts should be provided. This study aimed to describe how to produce performing arts learning design in kindergarten school by utilizing local cultural excellence knowledge sources (local genius knowledge) of Trawas district of Mojokerto with concept of integrated learning. This study used qualitative phenomenological research. The results show that during pandemic students can still learn the art performing by using online media (WhatsApp video call) so students can be more creative and discover the latest movements with the assistance of parents at home. The modeling strategy by inserting the Bantengan traditional performance as local genius of Mojokerto made the art performing learning in the kindergarten school was more meaningful. The integration of strategy and media with local genius of implemented in the school was potentially adopted larger.